Soft tissue sarcoma of the upper extremity: oncological and functional results after surgery - EROL, BÜLENT; ŞANAL TOPRAK, CANAN (SAGE PUBLICATIONS LTD, 2021)
This retrospective study evaluates outcomes after treatment of upper-extremity soft tissue sarcoma in 44 patients. We re-resected 19 tumours that had been resected elsewhere without adequate preoperative planning, and we made 25 well-planned primary resections. Four patients in the unplanned group and five in the planned group eventually received amputations. Thirty-three patients were alive at a median follow-up time of 33 months (IQR 18 to 57). Tumour size > 7 cm, tumour Grade 3 and the presence of distant organ metastases were the main factors affecting the oncological outcomes. We found no statistical differences between the planning groups. Functional outcomes and quality of life were significantly worse after amputation or major nerve resections. We conclude with this sized sample that the lack of planning in itself did not influence the final results, but there were differences in tumour size, grade and localization between the groups that may play a role.
Keywords: Upper extremity; soft tissue sarcoma; unplanned surgery; oncological results; bimanual extremity functions; quality of life; FOREARM; QUICKDASH; OUTCOMES; TUMORS; SF-36; HAND